2014
DOI: 10.1097/ico.0000000000000258
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Systemic Tacrolimus in High-Risk Penetrating Keratoplasty After Graft Failure With Systemic Cyclosporine

Abstract: Treatment with systemic tacrolimus is possibly safe and effective in reducing graft rejection and prolonging graft survival in patients with high-risk PKP after graft failure with systemic CsA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 31 publications
0
22
0
2
Order By: Relevance
“…Eight patients experienced rejection episodes while on tacrolimus, and this led to graft failure in 5 patients. In another study, Yamazoe et al 161 used systemic tacrolimus in patients with HR keratplasty who developed graft failure despite treatment with systemic CsA. They observed significantly fewer graft rejection episodes and longer graft survival with tacrolimus than with CsA.…”
Section: Management Of High-risk Corneal Transplantationmentioning
confidence: 99%
“…Eight patients experienced rejection episodes while on tacrolimus, and this led to graft failure in 5 patients. In another study, Yamazoe et al 161 used systemic tacrolimus in patients with HR keratplasty who developed graft failure despite treatment with systemic CsA. They observed significantly fewer graft rejection episodes and longer graft survival with tacrolimus than with CsA.…”
Section: Management Of High-risk Corneal Transplantationmentioning
confidence: 99%
“…Systemic use of tacrolimus was also evaluated. It may be a safe and effective therapeutic modality in reducing rejection and prolonging graft survival in patients with high-risk keratoplasty [53, 62, 63]. …”
Section: Reviewmentioning
confidence: 99%
“…Yamazoe et al . reported that after tacrolimus systemic administration for treating high‐risk penetrating keratoplasty after graft failure with systemic cyclosporine in clinic, one of the patients suffered renal dysfunction and another one had muscle pain and fatigue.…”
Section: The Drug Treatment Of Cnvmentioning
confidence: 99%